2005
DOI: 10.1291/hypres.28.837
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypoxia Accelerates the Progression of Atherosclerosis in Apolipoprotein E-Knockout Mice

Abstract: The aim of this study was to investigate the effect of chronic hypoxia on the development and progression of atherosclerosis in apolipoprotein E-knockout (apoE-KO) mice. Male and female apoE-KO mice (6 weeks old) and age-and sex-matched wild-type mice were kept under hypoxic conditions (10.0 ± 0.5% O2) in a gas chamber or in room air for 3 weeks. Aortic atherosclerotic plaque was not observed in wild-type mice under normoxic or hypoxic conditions. In the apoE-KO mice, however, hypoxia induced proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 41 publications
(30 reference statements)
4
56
2
Order By: Relevance
“…Oxidative stress initiates several processes involved in atherogenesis, including expression of adhesion molecules, stimulation of VSMC proliferation and migration, apoptosis in the endothelium, oxidation of lipids, activation of matrix metalloproteinases, and altered vasomotor activity (27,28). We confirmed that AT1 deficiency reduced the plasma concentration of 8-isoprostane.…”
Section: Discussionsupporting
confidence: 70%
“…Oxidative stress initiates several processes involved in atherogenesis, including expression of adhesion molecules, stimulation of VSMC proliferation and migration, apoptosis in the endothelium, oxidation of lipids, activation of matrix metalloproteinases, and altered vasomotor activity (27,28). We confirmed that AT1 deficiency reduced the plasma concentration of 8-isoprostane.…”
Section: Discussionsupporting
confidence: 70%
“…Rodent studies have been equivocal. Chronic hypoxia accelerated the development of atherosclerosis in apoE gene-deleted (apoE -/-) mice, along with increased reactive O 2 -production and activated matrix metalloproteinase-9 (MMP-9) in the aorta according to Nakano et al [8]. In any event, chronic hypoxia-related effects should involve hypoxia-inducible factor 1-alpha (HIF-1α).…”
mentioning
confidence: 99%
“…It has also been reported that hypoxia accelerates the progression of atherosclerosis (47,62) and modulates vascular remodeling after arterial injury (46). Several studies have provided evidence of hypoxia within the arterial wall in atherosclerosis in an animal model (29) and human disease (63,64).…”
Section: Inflammatory Responses To Arteriosclerosis and Vascular Remomentioning
confidence: 99%
“…ROS generation during hypoxia is reported to be produced from mitochondrial complex II, NADPH oxidase, and xanthine oxidoreductase (42 -45). Therefore, the effects of hypoxia-mediated generation of ROS on atherosclerosis suggest aggravated intimal thickening compared to normoxic exposure of a ballooninjured rabbit (46) and apolipoprotein E-deficient mice (47). Although these studies have shown an effect of low oxygen levels on the initiation and aggravation of vascular remodeling, it remains unclear how decreased oxygen in the pathophysiological microenvironment causes vascular remodeling.…”
Section: Vascular Responses To Hypoxia In Development Of Vascular Remmentioning
confidence: 99%